Genetic diversity of Rhizoctonia solaniAG-3PT, the etiological cause of stem canker and black scurf in Colombian potatoes (2021)
Stem canker and black scurf are potato diseases caused by the fungus Rhizoctonia solani, anastomosisgroup 3 (AG-3PT). This fungus affects potato roots, stems, and tubers, reducing crop yields. This study aimsto determine the genetic diversity of R. solaniAG-3PT obtained from the Colombian departments of Antioquia, Boyacá, and Cundinamarca. Restrictionfragment lengthpolymorphism(RFLP) analysis of the ITS-5.8S ribosomal DNA region allowed the differentiation and specific identification of AG-3PT and AG2-1 anastomosis groups. These results confirm that AG-3PT is the primary causative agent and etiologicalorigin of stem canker and black scurf in Colombia. Two distinct subgroups within R. solaniAG-3PT were identified using random amplified microsatellite markers (RAMs); AG-3PT (A) shares a similarity index of 78%, and AG-3PT (B) shares a similarity of 79% among its isolates. These subgroups were not linked to a geographical origin but to the AG group to which they belong. Nei’s genetic diversity [D] of 0.25 confirmed the high genetic diversity for AG-3PT through RAMsanalysis, related to a high evolutive potential within the AG-3PT group in Colombia. Finally, the R. solaniAG-3PT fungus obtained from Cundinamarca had the adaptative potential to emerge as a pathogen of Solanum phurejain Colombia, possibly due tothe similarity between pathosystems.